Large-scale land deals and social conflict: Evidence and policy implications - Alexander de Juan; Daniel Geissel; Jann Lay; Rebecca Lohmann (German Institute of Global and Area Studies (GIGA), 2022)
How do large-scale land acquisitions (LSLAs) increase the risk of conflict, and what kind of policies can mitigate this effect? We address these questions with a systematic and policyoriented synthesis of prior research. First, we suggest a simple conceptual framework linking LSLAs to social conflict through relative deprivation. Second, we present empirical evidence on the associations between land investments and social conflict, drawing on preexisting quantitative and qualitative studies as well as on own descriptive analyses and case studies. Taken together, this evidence suggests that conflicts accompany a substantive share of LSLAs (10 to 20 percent). Specifically, contentious dynamics often start with violations of community interests, which spur largely peaceful community protests that trigger coercion and violence at the hands of armed actors associated with national governments and investors. Third, we develop a set of policy recommendations in highlighting the need for thorough regulatory frameworks, meaningful consultation, and full transparency.
Keywords: Q15; Q18; D74; 330; Sub-Saharan Africa; Southeast Asia; large-scale land acquisitions; social conflict; relative deprivation